PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, LAIN-LAIN PENDAPATAN DAERAH YANG SAH TERHADAP BELANJA DAERAH KOTA BALIKPAPAN - Christine April Dayanti Sitinjak; Juwari Juwari; Dwi Susilowati (Jurnal GeoEkonomi, 2021)
ABSTRACT This research aims to know the influece of simultaneus or partially variable Local Revenues, Balance Funds, Other Legitimate Income Toward Regional Expense on Balikpapan city. In year 2010-2018 obtained from the Office Regional Financial and Asset Management of Balikpapan. The technique of determination of sample in this study using saturated sample. Test result simultaneously that The effect of Local Revenues, Balance Funds, and Other Legitimate Income Toward Regional Expense on Balikpapan city. Collectively have a not significant influence on the Balikpapan city. Because Fhitung is smaller that Ftabel. While the test resulhts that partially Local Revenues has a positive effect and significant, Balance Funds has a positive effect and not significant, and Other Legitimate Income has a negative effect and not significant. Test resulhts that partially Local Revenues has a dominant influence Regional Expense on Balikpapan city because value thitung and the partial r most large compared to other variable second.